Co–In Bimetallic Hydroxide Nanosheet Arrays With Coexisting Hydroxyl and Metal Vacancies Anchored on Rod‐Like MOF Template for Enhanced Photocatalytic CO2 Reduction - Jingjuan Feng; Weiwei Li; Tianxia Chen; Zhaopeng Zeng; Meng Tian; Wenxin Ji; Yan Guo; Shixiong Min; Xiangyu Liu (Advanced Science, 2025)
Abstract Layered double hydroxides (LDHs) can serves as catalysts for CO2 photocatalytic reduction (CO2PR). However, the conventionally synthesized LDHs undergo undesired aggregation, which results in an insufficient number of active sites and limits the desirable electron transfer required for CO2PR. The metal‐organic framework (MOF) template‐grown LDHs demonstrate excellent promise for exploiting the strengths of both MOFs and LDHs. Herein, the in situ growth of MIL‐68(In)‐NH2 MOF‐templated Co–In bimetallic catalyst (CoIn‐LDH/MOF) having an ultrathin nanosheet morphology on the preserved rod‐like MOF template is demonstrated. Compared to the conventionally grown bimetallic LDH (CoIn‐LDH), CoIn‐LDH/MOF not only exposes more active sites but also possesses hydroxyl vacancies (VOH) and Co vacancies (VCo). Thus, CoIn‐LDH/MOF performs a higher CO generation rate of 2320 µmol g−1 h−1 during CO2PR, demonstrating improved activity and selectivity than those in CoIn‐LDH. Experiments coupled with calculations reveal that the CoIn‐LDH/MOF‐driven CO2PR follows the *COOH pathway. The lower energy barriers for the formation of *COOH and CO(g) can be attributed to the coexistence of VOH and VCo in CoIn‐LDH/MOF, effectively promoting charge transfer and enhancing CO2PR performance. This study provides a new strategy to obtain high‐performant LDH‐based catalysts with improved morphology.